2020
DOI: 10.1186/s13104-020-4939-z
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical quality of water and health risks associated with consumption of African lung fish (Protopterus annectens) from Nyabarongo and Nyabugogo rivers, Rwanda

Abstract: Objective: To determine the quality of water, heavy metal content of edible muscles of a piscivorous fish (Protopterus annectens) and assess the health risks associated with using water and consumption of P. annectens from Nyabarongo and Nyabugogo rivers of Rwanda. Results: All the water quality parameters were within World Health Organization's acceptable limits except total nitrogen, iron, manganese and lead levels. Edible muscles of Protopterus annectens contained 272.8 ± 0.36, 292.2 ± 0.25, 8.8 ± 0.36, 135… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 10 publications
2
12
1
Order By: Relevance
“…The values were not significantly different between the dry and wet seasons, and that of Mubuku River. The pH values obtained in this study were comparable to 7.06 and 7.03, 6.2-8.0, 7.96-8.22, 6.6-7.5, 5.85-7.60 and 8.05-8.30 reported for water from NR [19,44], River Mohokare of Lesotho [45], Nyabugogo and Nyabarongo rivers, Rwanda [42], Aturukuku River [46], Nyamugasani River [47] and Rwimi River of Uganda [47,48]. Interestingly, the pH values were slightly higher than 5.60-6.32 and 5.58-6.80 reported for water sampled from NR and Mubuku River of Uganda reported by Mukisa et al [48].…”
Section: Seasonal Variations In Physicochemical Parameters Of Water I...supporting
confidence: 87%
See 1 more Smart Citation
“…The values were not significantly different between the dry and wet seasons, and that of Mubuku River. The pH values obtained in this study were comparable to 7.06 and 7.03, 6.2-8.0, 7.96-8.22, 6.6-7.5, 5.85-7.60 and 8.05-8.30 reported for water from NR [19,44], River Mohokare of Lesotho [45], Nyabugogo and Nyabarongo rivers, Rwanda [42], Aturukuku River [46], Nyamugasani River [47] and Rwimi River of Uganda [47,48]. Interestingly, the pH values were slightly higher than 5.60-6.32 and 5.58-6.80 reported for water sampled from NR and Mubuku River of Uganda reported by Mukisa et al [48].…”
Section: Seasonal Variations In Physicochemical Parameters Of Water I...supporting
confidence: 87%
“…The cancer risk (CR) estimated as the incremental lifetime cancer risk for the carcinogenic heavy metals (Pb, Cd, Cr and As) were calculated as the product of ADD ing and the ingestion cancer slope factor (CSF) using Equation 5. Consequently, the total cancer risk (TCR) from ingestion of the carcinogenic HMs in water was calculated using Equation 6 suggested by preceding authors [35,42].…”
Section: Cancer Risk Assessmentmentioning
confidence: 99%
“…Overall, the consumption of the fish from all the sites pose no cancer risk to the consumers irrespective of their age group. However, the study in Rwanda showed that intake of fish can cause cancer to children and adults due to high chromium and lead in the edible fish muscles with values greater than 1 × 10 −4 [ 108 ]. Results from this study agrees with the findings of Ahmed et al [ 29 ] that children are more sensitive and prone to risk of trace metals contamination in fish muscles than adults.…”
Section: Resultsmentioning
confidence: 99%
“…Apparatus and reagents were those previously used [8,10,14]. Study approval was granted by Department of Chemistry, Kyambogo University, Uganda (Approval No.…”
Section: Materials and Study Approvalmentioning
confidence: 99%